AKTUALISASI PENGEMBANGAN DAN PELINDUNGAN BAHASA DAN SASTRA DI BALAI BAHASA JAWA TENGAH - Anisa Fitri; Suhardi Suhardi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
This paper aims to discuss the work program carried out by the Central Java Provincial Language Center in realizing the development and protection of Indonesian language and literature in Central Java. This study uses qualitative methods with descriptive analysis. Data analysis techniques were carried out with the stages of data reduction, data presentation, and drawing conclusions. The subject of this research is the Language Center of Central Java Province. The object of his research is the activities of the Central Java Provincial Language Center in realizing the development and protection of Indonesian language and literature in Central Java for the 2020-2022 period. The results of the study show that in language development efforts are made to modernize the language through enriching vocabulary, strengthening and standardizing the language system, and developing language tunings. The Central Java Provincial Language Center utilizes all available media and resources as a means of realizing the development, fostering and protection of language and literature. Implementation of the work program of the Central Java Provincial Language Center can increase positive attitudes towards Indonesian language norms and preserve regional literature.